c.2 - Gupta, S. P. (Bombay, 1989)
This book provides a unique examination both from the theoretical as well as from the practical angles, India's thirty-five year planning process. The author draws upon his actual working experience while work ing as Perspective Plan adviser and his as sociation with the preparation of the Sixth Five-Year Plan (1980-85) and the Seventh Five-Year Plan (1986-90) of India. He has presented an evaluation of past six plans and the future problems and the task the Seventh Plan is facing. The Indian deve lopment strategy now stands at the cross roads. In some respects, the difficult phase of her development is over; the country has developed a potential base for a take off. But in some others she is now facing the most difficult phase of development. The strategy pursued in the past, in con junction with a set of objectives, has achieved the basic prerequisite for growth. The country's economic structure has grown out of its infancy and reached adulthood. For further advancement she must now play the game of an adult. In deed, old strategy needs a re-examination, failing which the country may get caught in a low-equilibrium trap. But this restruc turing is rather painful. The long-term and immediate problems may ask for a trade off. Many of the old and accepted goals may conflict with new strategies and in struments to take the country to a higher, balanced path. The interdependence of the world economy is increasing. The pangs of isolation are damaging most economies. A development strategy based on a 'closed economy' is becoming obsolete. Pragmat ism is becoming the keyword in all planned economies. Many of these aspects are touched in this volume.
Keywords: Planning and development